2008
DOI: 10.1021/ja711422h
|View full text |Cite
|
Sign up to set email alerts
|

Site-Selective Guest Inclusion in Molecular Networks of Butadiyne-Bridged Pyridino and Benzeno Square Macrocycles on a Surface

Abstract: We present here the formation of a modular 2D molecular network composed of two different types of square-shaped butadiyne-bridged macrocycles, having intrinsic molecular voids, aligned alternately at the solid-liquid interface. Site-selective inclusion of a guest cation took place at every other molecular void in the molecular network with two different recognition sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
60
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 70 publications
(61 citation statements)
references
References 22 publications
1
60
0
Order By: Relevance
“…Complex 1a·3 and cyclophane 2a randomly mixed on the surface forming the non-porous A pattern, 18 which is not surprising in view of the same substituents in these macrocycles. Occasionally, randomly mixed domains were observed in the case of a mixture of 1c·3 and cyclophane 2c (on an average 17%, Figure S4b), in addition to segregated domains of each component.…”
Section: Molecular Network Formed By Bimolecular Mixtures Of Pyridinmentioning
confidence: 89%
See 4 more Smart Citations
“…Complex 1a·3 and cyclophane 2a randomly mixed on the surface forming the non-porous A pattern, 18 which is not surprising in view of the same substituents in these macrocycles. Occasionally, randomly mixed domains were observed in the case of a mixture of 1c·3 and cyclophane 2c (on an average 17%, Figure S4b), in addition to segregated domains of each component.…”
Section: Molecular Network Formed By Bimolecular Mixtures Of Pyridinmentioning
confidence: 89%
“…17 Previously, we reported that butadiyne-bridged pyridino and benzo square macrocycles 1a and 2c (Scheme 1) form a molecular network in which 1a and 2c aligned alternately in one-FULL PAPER dimension (1D alternating pattern) via attractive dipole-dipole interactions between the ester groups of 1a and the ether groups of 2c. 18 Note that this alternating network structure is different from the pattern formed by each single component (1a or 2c). Tropylium ion selectively binds 1a forming a 1 to 1 complex on the graphite surface.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations